2020
DOI: 10.1111/jace.17349
|View full text |Cite
|
Sign up to set email alerts
|

Templated grain growth of high coercive field CuO‐doped textured PYN‐PMN‐PT ceramics

Abstract: This paper explores the templated grain growth and texturing of Pb(Yb1/2Nb1/2)O3‐Pb(Mg1/3Nb2/3)O3‐PbTiO3 (PYN‐PMN‐PT) ceramics. A PbO‐CuO liquid phase was determined to substantially increase the growth of PYN‐PMN‐PT on barium titanate template particles. Texturing resulted in an 83% enhancement in strain behavior (754 pm/V) compared with random PYN‐PMN‐PT ceramics (413 pm/V). The increased Pb(Yb1/2Nb1/2)O3 (PYN) content of textured 21PYN‐41PMN‐38PT resulted in a high coercive field of 13.9 kV/cm. Residual bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The ε r in textured ceramics is almost twice as much as that in untextured ceramics, which may be due to the presence of the “4R” engineered domain structure in [001]‐oriented where domain rotation is much easier. Since of the presence of orientation, the permittivity and longitudinal piezoelectric constant d 33 poled along the [00 1] or [011] direction are higher than those of the [111] direction in rhombohedral phase 28,36 Besides, the increase of tanδ for textured ceramic may be attributed to the increased non‐180° domain wall motion associated with the enhanced strain behavior 37 …”
Section: Resultsmentioning
confidence: 99%
“…The ε r in textured ceramics is almost twice as much as that in untextured ceramics, which may be due to the presence of the “4R” engineered domain structure in [001]‐oriented where domain rotation is much easier. Since of the presence of orientation, the permittivity and longitudinal piezoelectric constant d 33 poled along the [00 1] or [011] direction are higher than those of the [111] direction in rhombohedral phase 28,36 Besides, the increase of tanδ for textured ceramic may be attributed to the increased non‐180° domain wall motion associated with the enhanced strain behavior 37 …”
Section: Resultsmentioning
confidence: 99%
“…Although various templates of BaTiO 3 , 4,5 SrTiO 3 , 6,7 Bi 4 Ti 3 O 12 , 8,9 PbTiO 3 , 10,11 etc., 12,13 have been reported to be useful for achievement of superior piezoelectric ceramics; overdosed templates, because heterogeneous templates act as impurities, have resulted in deterioration of piezoelectricity in matrix ceramics. In particular, the plate‐like BaTiO 3 template has been widely utilized for PbTiO 3 (PT)‐based piezoelectric ceramics such as Pb(Mg 1/3 Nb 2/3 )O 3 ‐PbTiO 3 , 14–16 Pb(In 1/2 Nb 1/2 )O 3 ‐Pb(Mg 1/3 Nb 2/3 )O 3 ‐PbTiO 3 , 17,18 Pb(Yb 1/2 Nb 1/2 )O 3 ‐Pb(Mg 1/3 Nb 2/3 )O 3 ‐PbTiO 3 , 19,20 Pb[(Zn 0.4 Ni 0.6 ) 1/3 Nb 2/3 ]O 3 ‐PbZrO 3 ‐PbTiO 3 , 21 and Pb(Ni 1/3 Nb 2/3 )O 3 ‐PbZrO 3 ‐PbTiO 3 22 ceramics to achieve textured structures. However, given the heterogeneity between the template and matrix ceramic, PT platelets are strongly recommended to realize better quality texture and piezoelectric properties of PT‐based piezoelectric ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Lead‐based ferroelectrics such as PZT and Pb(Mg 1/3 Nb 2/3 )O 3 ‐PbTiO 3 (PMN‐PT) have been well studied in their ceramic and single crystal forms due to their high piezoelectric responses that are desirable for sensor and actuator applications 6,25–32 . Yet, recent studies of ternary compositions such as Pb(Mg 1/3 Nb 2/3 )O 3 ‐PbZrO 3 ‐PbTiO 3 (PMN‐PZ‐PT), Pb(Sc 1/2 Nb1/2)O 3 ‐PbZrO 3 ‐PbTiO 3 (PSN‐PZ‐PT), Pb(In 1/2 Nb 1/2 )O 3 ‐Pb(Mg 1/3 Nb 2/3 )O 3 ‐PbTiO 3 (PIN‐PMN‐PT) have found that they generally exhibit superior piezoelectric response and temperature stability than binary compositions 33–36 . This paper focuses on studying the electromechanical mechanism in PMN‐PT textured ceramics, as the piezoelectric properties and structure of the system in ceramic and single crystal form are more thoroughly understood than ternary compositions, making a comparison to the changes imposed from crystallographic texture more clear.…”
Section: Introductionmentioning
confidence: 99%